1987
DOI: 10.1111/j.1365-246x.1987.tb00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractal structure of spatial distribution of microfracturing in rock

Abstract: A constant stress fracture experiment of Oshima granite was carried out at the confining pressure of 40MPa. Hypocentres of 2064 acoustic emissions were located during the experiment. Using the 'correlation integral', we found that the spatial distribution of hypocentres of acoustic emission is a fractal, and that the fractal dimension decreases with the evolution of rock fracturing. The spatial distribution of earthquake's hypocentres reveals fractals ranging from regional to worldwide distribution. If we extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
157
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(178 citation statements)
references
References 10 publications
17
157
1
3
Order By: Relevance
“…In the present study, following Hirata et al (1987), we used the correlation integral method for analysis of the spatial distribution of synthetic seismicity. Uritsky and Troyan (1998) studied the behaviour of fractal dimension, calculated by the box-counting method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, following Hirata et al (1987), we used the correlation integral method for analysis of the spatial distribution of synthetic seismicity. Uritsky and Troyan (1998) studied the behaviour of fractal dimension, calculated by the box-counting method.…”
Section: Discussionmentioning
confidence: 99%
“…The gradual decreasing of the correlation exponent of the spatial distribution of acoustic shocks was observed by Hirata et al (1987) during the destruction of granite sample. The correlation exponent is a kind of fractal dimension, which can be calculated for the group of points according to the following algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Ponomarev et al (1997) found a significant decrease in fractal dimension just before the global instability in the laboratory experiment. Then, the spatial distribution of acoustic emissions of rock fracture experiment was used to obtain a decrease in fractal dimension before the rupture (Jaeger and Cook, 1976;Hirata et al, 1987). The temporal evolution of acoustic emissions was also studied by Hirata (1987), who found that the temporal evolution of acoustic emissions becomes fractal over a range from microfracture to an EQ.…”
Section: The Importance Of Fractal Analysis In the Nonlinear Process mentioning
confidence: 99%
“…Based on observed data, Hirata (1987) and Yamamoto et al (1993) found that fractures are not randomly distributed in space, but spatially clustered. The spatial clustering patterns could be described by fractals (Hirata, 1987;Yamamoto et al, 1993).…”
Section: Implications and Limitations Of The Data Analysismentioning
confidence: 99%